Legal Analysis of the Notary's Obligation to Affix the Appearers' Fingerprints on the Minuta (Original) Deed - WD. Sitti Masita; MH Ingratubun; Herniati Herniati (Social Science Academic, 2026)
This research aims to identify and analyze the legal basis obliging a notary to require appearers to affix their fingerprints on the Minuta Akta, viewed from the resolution of norm conflict and the principle of legal certainty, and to examine the legal risks a notary faces, along with their implications for evidentiary strength, when this obligation is neglected. The research employs a normative legal method through statute and conceptual approaches, drawing on primary, secondary, and tertiary legal materials analyzed through prescriptive-qualitative reasoning and deductive syllogism. The results show that Article 16 paragraph (1) letter c of the Notary Position Law imperatively binds the notary, and its apparent tension with Articles 1 and 38 is resolved through the principle of lex posterior derogat legi priori, positioning the fingerprint as a complement to, not a substitute for, the signature. Neglecting this obligation carries cumulative risk: the deed's evidentiary force may be degraded to that of a private instrument under Article 1869 of the Civil Code, while the notary may face administrative sanction and ethical censure. These findings affirm that fingerprinting functions as a constitutive safeguard of authenticity essential to legal certainty in notarial practice.